Disruption of the pro-inflammatory, anti-inflammatory cytokines and tight junction proteins expression, associated with changes of the composition of the gut microbiota in patients with irritable bowel syndrome. - V Ivashkin (Public Library of Science (PLoS), 2021)
Background Irritable bowel syndrome (IBS) is a pathologic condition characterized by changes in gut microbiome composition, low-grade inflammation, and disruption of intestinal wall permeability. The interaction between the gut microbiome and the disease manifestation remains unclear. The changing of tight junction proteins and cytokines expression throughout the gastrointestinal tract in IBS patients has not been studied yet. Aim of the study To assess the changes of gut microbiome composition, tight junction proteins, and cytokines expression of intestinal mucosa from the duodenum to the distal part of the colon in IBS patients and healthy volunteers. Methods In 31 IBS patients (16 patients with IBS-D; 15 patients with IBS-C) and 10 healthy volunteers the expression of CLD-2, CLD-3, CLD-5, IL-2, IL-10, and TNF-α in mucosal biopsy specimens was determined by morphological and immune-histochemical methods. The qualitative and quantitative composition of the intestinal microbiota was assessed based on 16S rRNA gene sequencing in both groups of patients. Results The expression of IL-2 and TNF-α was significantly increased in IBS patients compared with the controls (p<0.001), with a gradual increase from the duodenum to the sigmoid colon. The expression of IL-10, CLD-3, and CLD-5 in mucosal biopsy specimens of these patients was lower than in the control group (p<0.001). Increased ratios of Bacteroidetes and decreased ratios of Firmicutes were noted in IBS patients compared to healthy volunteers (p<0.05). Conclusion IBS patients have impaired gut permeability and persisting low-grade inflammation throughout the gastrointestinal tract. Changes in the gut microbiota may support or exacerbate these changes.